Sarcomatoid Urothelial Carcinoma of Urinary Bladder – A Rare Case Report (Indian Journal of Case Reports, 2016)
Sarcomatoid variant of urothelial carcinoma of urinary bladder is a rare tumor which exhibits epithelial and mesenchymal differentiation of tumor cells both morphologically and immunohistochemically. Cyclophosphamide treatment and radiation therapy are associated with this tumors. This tumor is considered to be the aggressive variant of transitional cell carcinomas of the bladder. Treatment for this aggressive tumor is radical surgical excision with chemoradiation. We report a case of 47-year-female presenting with dysuria and hematuria. On imaging, heterogeneously enhancing hyperdense lesion in bladder was noted which was diagnosed as sarcomatoid urothelial carcinoma on histopathological examination.